The effect of preloading statins prior to primary reperfusion on in-hospital mortality risk in a contemporary large-scale cohort of patients with ST-elevation myocardial infarction. (25th November 2020) - Fu, R; Song, C.X; Li, X.D; Yang, Y.J
Abstract: Background: The benefit of statins in secondary prevention of patients stabilized after acute coronary syndrome (ACS) has been well established. However, the benefit of preloading statins, i.e. high-intensity statins prior to reperfusion therapy remains unclear. Most previous studies included all types of ACS patients, and subgroup analysis indicated the benefit of preloading statins was only seen in ST-elevation myocardial infarction (STEMI) patients who underwent percutaneous coronary intervention (PCI). However, the sample size of subgroup population was relatively small and such benefit requires further validation. Objective: To investigate the effect of loading dose of statins before primary reperfusion on 30-mortality in patients with STEMI. Methods: We enrolled patients in China Acute Myocardial Infarction (CAMI) registry from January 2013 to September 2014. CAMI registry was a prospective multicenter registry of patients with acute acute myocardial infarction in China. Patients were divided into two groups according to statins usage: preloading group and control group. Patients in preloading group received loading does of statins before primary reperfusion and during hospitalization. Patients in control group did not receive statins during hospitalization or at discharge. Primary outcome was in-hospital mortality. Baseline characteristics, angiographic characteristics and outcome were compared between groups. Propensity score (PS) matching was used to mitigate baseline differences between groups and examine the association between preloading statins on in-hospital mortality risk. The following variables were used to establish PS matching score: age, sex, classification of hospitals, clinical presentation (heart failure at presentation, cardiac shock, cardiac arrest, Killip classification), hypertension, diabetes, prior angina, prior myocardial infarction history, prior stroke, initial treatment. Results: A total of 1169 patients were enrolled in control group and 6795 in preloading group. A total of 833 patients (334 in control group and 499 in preloading group) died during hospitalization. Compared with control group, preloading group were younger, more likely to be male and present with Killip I classification. The proportion of hypertension and diabetes were higher in preloading group. After PS matching, all the variables used to generate PS score were well balanced. In the PS-matched cohort, 30-day mortality risk was 26.3% (292/1112) in the control group and 11.9% (132/1112) in the preloading group (p<0.0001). Conclusions: The current study found preloading statins treatment prior to reperfusion therapy reduced in-hospital mortality risk in a large-scale contemporary cohort of patients with STEMI. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Chinese Academy of Medical Sciences